Impacts from tourism development and agriculture on forest degradation in Thap Lan National Park and adjacent areas - Pongpattananurak, Nantachai (Agriculture and Natural Resources, 2018)
The overlapping area between Thap Lan National Park and Thai Samakkhi subdistrict is a popular tourist destination in Nakorn Ratchasima province, Thailand and in recent decades, this area has been extensively developed for both tourism and agriculture. However, such changes have violated Thai national law since most of the developed areas are within Thap Lan National Park. Therefore, the effect of these developments on the natural forest community was studied. A sample size of 111 temporary plots was set up for collecting data on native tree species and exotic plant species of all life-forms. The findings revealed that the vegetation cover could be categorized into two main groups: 1) natural plant communities, consisting of dry evergreen forests, mixed deciduous forests and secondary forests; and 2) plant communities resulting from anthropogenic disturbances, consisting of forest plantations, field crops, orchards, resort parcels, and temple vicinities. The study also found that tree sapling and tree seedling densities and the percentage ground cover were significantly lower in areas developed for tourism and agriculture than in areas of natural plant communities. This reflected the inability of native species to regenerate and disperse naturally in this modified landscape. In addition, in the humandeveloped areas, several introduced, invasive, alien plants and weeds in field crop, orchard and resort plant communities were found. The development of tourism activities and agriculture were the major factors which substantially threatened the sustainability of the natural ecosystem of the tropical forests in this region.